NEEDS ANALYSIS IN DESIGNING ENGLISH FOR YOUNG LEARNERS’ MATERIAL AT RUBIK SOCIAL SCHOOL - Euis Kurniasih (Journal of English Language Teaching and Literature (JELTL), 2022)
Many social institutions concerning on education field open English classes for children by recruiting volunteer teachers. However, this voluntary English teaching activity makes the materials provided are not well structured so that the preparation of teaching materials is needed based on the needs of the learners involved. This research aims to identify the English learning needs in Rubik Social School. The method applied are observation, questionnaires and interviews. The subject of research is the students and voluntary teachers. The results of the study include the target needs and learning needs. The target of English learning needs at the Rubik Social School is to support English subjects taught in formal schools and become the basis of skills for further education. The learning materials needed are simple vocabularies and expressions in which topics are close to children such as parts of the body, colours, family, fruits and vegetables and others. English learning is held in a face-to-face meeting and taught by voluntary non-native speaker teachers every week. The results of this study should be continued as material for the syllabus and teaching materials.